VISUALISASI BUNGA MAWAR DALAM HIASAN DINDING TEKNIK RENDA, SULAM DAN BORDIR - FITRI LIANI, Dra. Ernis, M.Pd., Drs. Erwin A, M.Sn. (Universitas Negeri Padang, 2017)
Roses are ornamental plantswith stems that have thorns. Many planted in the garden and most sold in the flower shop as cut flowers or sow flowers. This flower is valuable because of its beauty and aroma, as well as useful and has manybenefits. Roses can almost be found in all countries around the world, so dubbed as the “Queen of all flowers”. The beauty of the rose is expressive make the author interestedto visualize it in the form of wall decoration. The metod of creating this work is made through three stages through lace, embroidery and embroidery techniques. Sketches made manually with roses as the main object, the material used is black and red velvet fabric, yarn used are lace thread, embroidery thread, and embroidery thread, with various colors. Roses are made with lace techniques, leaves with embroidery techniques, while the background embroidered with a drag technique. The seven works produced are titled respectively ie Gentleness, Complement, Joy, Hope, Passion, Tranquility and Purity.Keywords: Roses, lace, hand embroidered, embroidery.